Descending spinal cord volleys evoked by transcranial magnetic and electrical stimulation of the motor cortex leg area in conscious humans - Lazzaro, V Di (Blackwell Science Inc, 2001)
1. Descending corticospinal volleys evoked after transcranial magnetic or electrical stimulation of the leg area of the motor cortex were recorded from an electrode in the spinal epidural space of six conscious patients who had electrodes implanted for treatment of chronic pain, and from one anaesthetised patient undergoing surgery for a spinal tumour. 2. At threshold, the shortest-latency volley (L1 volley) was evoked by stimulation with an anode 2 cm lateral to the vertex. Anodal stimulation at the vertex also elicited a volley at this latency in two patients, but in the other patients the first volley evoked appeared 1—1.3 ms later (L2 volley), at the same latency as the initial volley evoked by magnetic stimulation. High-intensity stimulation of any type could evoke both the L1 and L2 waves as well as later ones (L3, L4, etc.) that had a periodicity of about 1.5 ms. 3. Voluntary contraction increased the amplitude of the L2 and later volleys, but had no effect on the L1 volley. 4. Intracortical inhibition between pairs of magnetic stimuli resulted in clear suppression of the L4 and later waves. The L2 and L3 waves were unaffected. 5. In the anaesthetised patient the L1 volley occurred 1.7 ms later than the volley produced by transmastoid stimulation of the corticospinal pathways in the brainstem. 6. The L1 volley is likely to be a D wave produced by the direct activation of pyramidal axons in the subcortical white matter; the L2 and later volleys are likely to be I waves produced by the trans-synaptic activation of corticospinal neurones. The implication is that electrical stimulation with an anode at the vertex is more likely to evoke I waves preferentially than stimulation over the hand area. A more secure way to ensure D wave activation of corticospinal fibres from the leg area is to place the anode 2 cm lateral to the vertex.